Effect of aspirin on osteogenic differentiation and gene expression profiles in periodontal ligament stem cells / Fazliny Abd. Rahman - Fazliny, Abd. Rahman (2017)
Periodontal ligament (PDL) contains a unique population of mesenchymal stem cells (MSCs), also known as PDL stem cells (PDLSCs). The regenerative properties of PDLSCs hold great potential for its use in stem cells based therapy, particularly for periodontal or bone regeneration. Aspirin (ASA) is a widely used non-steroidal anti-inflammatory drug (NSAID) that has been reported to modulate a variety of diseases such as cardiovascular, diabetes and cancer. There have not been many studies examining the effect of ASA on stem cells, notably PDLSCs. The present study investigated the effects of ASA on the proliferation rate, osteogenic differentiation rate, expression of growth factor-associated genes and global gene expression profile in PDLSCs. MSCs from PDL were isolated from normal permanent human teeth (n=3). The MSCs identity was validated by immunophenotyping and tri-lineage differentiation capacity assays. The cell proliferation rate was measured through 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. PCR array was used to profile the expression of 84 growth-factor associated genes in PDLSCs upon ASA treatment. The effect of ASA on the osteogenic potential of PDLSCs was evaluated through mineralization assay, using Alizarin Red S (ARS) staining. Microarray analysis was used to study the effects of ASA (200, 500, and 1,000 μM) on the gene expression profiles in PDLSCs during osteogenic differentiation. The results indicated that ASA treatment affect PDLSCs proliferation rate. When grown in basal media, ASA reduced PDLSCs proliferation rate, in time (24, 48, and 72 hrs) and dose (10 to 10,000 μM) dependent manners. However, ASA (at 500 and 1000 μM) significantly increased PDLSCs proliferation and osteogenic differentiation rates when they were grown in osteogenic media. The PCR array analyses indicated that ASA was able to modulate the expression of growth factor-associated genes in PDLSCs. Using a fold-change (FC) of 2.0 as a threshold value, the analyses indicated that 19 growth factor-associated genes were differentially expressed (DE), of which 12 were upregulated and 7 were downregulated. Microarray study revealed that ASA was able to modulate PDLSCs gene expression profile. At 200 μM, 315 genes were DE, involving 151 upregulated and 164 downregulated genes. At 500 μM, 794 genes were DE, involving of 364 upregulated and 430 downregulated genes. At 1000 μM, the number of DE genes increased to 2035, of which 735 were upregulated and 1300 were downregulated. Bioinformatics analyses of the gene expression data revealed that the majority of DE genes (for 500 and 1,000 μM ASA treatment) are involved in osteogenic differentiation. The gene network analysis was carried out using Ingenuity Pathway Analysis (IPA) software, and this revealed that the number of gene groups involved in cell adhesion and extracellular matrix components were increased. Functional enrichment analysis using DAVID and PANTHER revealed a similar finding as revealed by IPA. The present study showed that ASA was able to modulate the expression of growth-factor associated genes and enhance osteogenic potential in PDLSCs. This study indicated that ASA could enhance PDLSCs functions and provide evidence for the potential use of ASA with PDLSCs for regenerative dentistry applications, particularly in the areas of periodontal health and regeneration.